The development of COVID-19 treatment - Yuan, Yongliang; Jiao, Baihai; Qu, Lili; Yang, Duomeng; Liu, Ruijuan (Frontiers in Immunology, 2023)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a pandemic named coronavirus disease 2019 (COVID-19) that has become the greatest worldwide public health threat of this century. Recent studies have unraveled numerous mysteries of SARS-CoV-2 pathogenesis and thus largely improved the studies of COVID-19 vaccines and therapeutic strategies. However, important questions remain regarding its therapy. In this review, the recent research advances on COVID-19 mechanism are quickly summarized. We mainly discuss current therapy strategies for COVID-19, with an emphasis on antiviral agents, neutralizing antibody therapies, Janus kinase inhibitors, and steroids. When necessary, specific mechanisms and the history of therapy are present, and representative strategies are described in detail. Finally, we discuss key outstanding questions regarding future directions of the development of COVID-19 treatment.